THE INFLUENCE OF PERSONAL SELLING AND E-WOM PERCEPTIONS OF BOPITASARI INSTAGRAM ACCOUNT TOWARDS SHOPEE PURCHASE INTENTION - Octavia Meiza Putri, Karina; Qurrota Ayyun, Primada; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The Shopee Affiliate Program is one of Shopee's digital marketing strategies that involves multiple parties. To retain the audience and compete with other competitors, affiliates need to create innovative marketing strategies that attract and drive the audience to act. Therefore, this study aims to analyze the influence of Personal Selling and E-WOM Perception towards Shopee Purchase Intention on Instagram. Although the streamer's persuasion strategy is relatively the same, the result is different. This studyaims to explain the effect of personal selling and E-WOM perceptions of affiliate marketer towards Shopee purchase intention using a quantitative approach trough an experimental method. The theory use in this study is the theory of reasoned action, with a purposive sampling technique involving 100 respondents. The results of hypotheses testing with multiple linear regression show that there is a significant influence between personal selling and E-WOM perceptions towards purchase intention.